2011
DOI: 10.1371/journal.pone.0015681
|View full text |Cite
|
Sign up to set email alerts
|

The Carrot or the Stick? Evaluation of Education and Enforcement as Management Tools for Human-Wildlife Conflicts

Abstract: Evidence-based decision-making is critical for implementing conservation actions, especially for human-wildlife conflicts, which have been increasing worldwide. Conservation practitioners recognize that long-term solutions should include altering human behaviors, and public education and enforcement of wildlife-related laws are two management actions frequently implemented, but with little empirical evidence evaluating their success. We used a system where human-black bear conflicts were common, to experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(69 citation statements)
references
References 41 publications
4
57
2
1
Order By: Relevance
“…Although previous research has shown that simply giving people more information is sometimes not enough for behavioral change (e.g., Baruch-Mordo, Breck, Wilson, & Broderick, 2011;Gore, Knuth, Scherer, & Curtis, 2008), we addressed a recognized need for better design of wildlife-related risk communication campaigns (Gore & Knuth, 2009) by investigating the role of message framing strategies, personal experience, and emotional responses in influencing intentions to adopt human-coyote conflict prevention behaviors. Our study provides insights to communication scholars and wildlife professionals alike in terms of the relative persuasiveness of different messages, as well as the different message strategies to use when communicating with targeted audiences.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has shown that simply giving people more information is sometimes not enough for behavioral change (e.g., Baruch-Mordo, Breck, Wilson, & Broderick, 2011;Gore, Knuth, Scherer, & Curtis, 2008), we addressed a recognized need for better design of wildlife-related risk communication campaigns (Gore & Knuth, 2009) by investigating the role of message framing strategies, personal experience, and emotional responses in influencing intentions to adopt human-coyote conflict prevention behaviors. Our study provides insights to communication scholars and wildlife professionals alike in terms of the relative persuasiveness of different messages, as well as the different message strategies to use when communicating with targeted audiences.…”
Section: Discussionmentioning
confidence: 99%
“…Both the human reaction to an event (positive versus negative) and the resulting behavior from an impact affect wildlife, e.g., decisions about pest control (Morzillo and Mertig 2011 a, b), and are influenced by complex interactions among human characteristics (Fig. 1c), such as environmental values and value orientations (e.g., Fulton et al 1996, Riley et al 2002, Zinn and Pierce 2002, Kaltenborn et al 2012, attitudes toward wildlife (e.g., Morzillo et al 2007, Krester et al 2009a, McDonald et al 2012, Urbanek et al 2013, interest in seeing wildlife (e.g., Morzillo et al 2007), attitudes toward particular species (e.g., Daniels and Kirkpatrick 2011), risk perception (Gore et al 2007), and other cognitive and motivational variables (Fulton et al 1996, Whittaker et al 2001, Baruch-Mordo et al 2011, Luther 2013. Collectively, these constructs influence and interact with each other, i.e., feedbacks, to form the basis for human cognitive and motivational perceptions and dynamics of human-wildlife relationships, i.e., "impact-based feedbacks" (e.g., Manfredo et al 2009, Decker et al 2012, and drivers of wildlife management as part of environmental policy ( Fig.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, humans may make landscape changes in attempt to repel wildlife, e.g., deer, from vegetation and other features (e.g., Barras and Seamans 2002, Gilsdorf et al 2002, Rondeau and Conrad 2003, Krester et al 2009b). Other methods include guidance, enforcement, and monitoring as mechanisms to change human behavior and minimize human-wildlife conflict, which may or may not be successful over time (Baruch-Mordo et al 2011). Regardless, as perceived by wildlife, those human-induced landscape changes will determine the return of an animal to the location of the event (Fig.…”
Section: Figmentioning
confidence: 99%
“…For example, "Some definitely want them outta there and it's all council's fault" (Interview #6). Trust and credibility can also diminish, and community frustration increase, if the managing agency is seen to be spending substantial resources on ineffective conflict mitigation measures [45,46]. On the other hand, the implementation of a management action can be evidence that residents' concerns have been heard, and that the land managers were prepared to try and assist them.…”
Section: Human-human Conflictmentioning
confidence: 99%